STRATEGIES FOR MANGROVE REHABILITATION IN AN ERODED COASTLINE OF SELANGOR, PENINSULAR MALAYSIA - Oswin D Stanley; Roy R Lewis III (JOURNAL OF COASTAL DEVELOPMENT, 2009)
Continuous mangrove ecosystem degradation and coastal erosion is observed along the coastline of SungaiHaji Dorani, (N 03038’36.6”; E 101000’37.3” to N 03038’37.9”; E 101000’34.0”) Selangor, PeninsularMalaysia. Foreshore mangrove plantation challenges below mean sea level are in progress in this highenergy coast. There are interventions of gabion breakwaters and geo-textile tubes to alleviate the wavevelocity striking the shore. The area between the breakwaters and coastline is chosen for mangroveplantation. The soil is fluid silt sludge with average clay, silt and sand proportion of 43.03 %, 351.8 % and5.14 % respectively. The maximum height of the tide recorded onshore was 2.8 m and in the middle of theplantation area the height of the water flooding is ±3.5 daily during tides. Number of plant species on theSAUH concrete revetment is 43 with 12 mangrove species and on the fringe reference mangroves is 27 with8 true mangrove species. This paper explains the method to identify the potential location for mangroverehabilitation, possibility of establishing mangroves on the seafront in the chosen area and conservation ofthe existing strip with 14 mangrove species. Overall sediment accretion since May 2008 is ±0.0037cm perannum which is considerably negligible. Opening out the earthen bunds along the coastline is the actualsolution for natural mangrove translocation and stabilization in this particular coastline, however, it is notpractically possible. Hence, we have studied an alternative strategy of rehabilitating mangroves at theelevation of +0.5 m to 1m MSL along this shoreline and also in an engineered firm sediment filled zone. Wepropose carrying out hydrological restoration in the natural habitats for survival and further naturalcolonization of mangroves.